Integration analysis of metabolome and transcriptome reveals the effect of exogenous supplementation with mixtures of vitamins ADE, zinc, and selenium on follicular growth and granulosa cells molecular metabolism in donkeys (Equus asinus) - Guo, Yajun; Zhao, Weisen; Li, Nan; Dai, Shizhen; Wu, Hao; Wu, Zhenlong; Zeng, Shenming (Frontiers in Veterinary Science, 2022)
Vitamins and microelements play essential roles in mammalian ovarian physiology, including follicle development, ovulation, and synthesis and secretion of hormones and growth factors. However, it is nevertheless elusive to what extent exogenous supplementation with mixtures of vitamins ADE, zinc (Zn), and selenium (Se) affects follicular growth and granulosa cells (GCs) molecular function. We herein investigated their effect on follicular growth and GCs physiological function. We showed that follicular growth and ovulation time was accelerated and shortened with the increases of vitamins ADE, Zn, and Se doses by continually monitoring and recording (one estrus cycle of about 21 days) with an ultrasound scanner. Integrated omics analysis showed that there was a sophisticated network relationship, correlation expression, and enrichment pathways of the genes and metabolites highly related to organic acids and their derivatives and lipid-like molecules. Quantitative real-time PCR (qPCR) results showed that vitamin D receptor (VDR), transient receptor potential cation channel subfamily m member 6 (TRPM6), transient receptor potential cation channel subfamily v member 6 (TRPV6), solute carrier family 5 member 1 (SLC5A1), arachidonate 5-lipoxygenase (ALOX5), steroidogenic acute regulatory protein (STAR), prostaglandin-endoperoxide synthase 2 (PTGS2), and insulin like growth factor 1 (IGF-1) had a strong correlation between the transcriptome data. Combined multi-omics analysis revealed that the protein digestion and absorption, ABC transporters, biosynthesis of amino acids, aminoacyl-tRNA biosynthesis, mineral absorption, alanine, aspartate and glutamate metabolism, glycine, serine and threonine metabolism, arginine biosynthesis, and ovarian steroidogenesis were significantly enriched. We focused on the gene-metabolite interactions in ovarian steroidogenesis, founding that insulin receptor (INSR), phospholipase a2 group IVA (PLA2G4A), adenylate cyclase 6 (ADCY6), cytochrome p450 family 1 subfamily b member 1 (CYP1B1), protein kinase camp-activated catalytic subunit beta (PRKACB), cytochrome p450 family 17 subfamily a member 1 (CYP17A1), and phospholipase a2 group IVF (PLA2G4F) were negatively correlated with β-estradiol (E2), progesterone (P4), and testosterone (T) (P < 0.05). while ALOX5 was a positive correlation with E2, P4, and T (P < 0.05); cytochrome p450 family 19 subfamily a member 1 (CYP19A1) was a negative correlation with cholesterol (P < 0.01). In mineral absorption, our findings further demonstrated that there was a positive correlation between solute carrier family 26 member 6 (SLC26A6), SLC5A1, and solute carrier family 6 member 19 (SLC6A19) with Glycine and L-methionine. Solute carrier family 40 member 1 (SLC40A1) was a negative correlation with Glycine and L-methionine (P < 0.01). TRPV6 and ATPase Na+/K+ transporting subunit alpha 1 (ATP1A1) were positively associated with Glycine (P < 0.05); while ATPase Na+/K+ transporting subunit beta 3 (ATP1B3) and cytochrome b reductase 1 (CYBRD1) were negatively related to L-methionine (P < 0.05). These outcomes suggested that the vitamins ADE, Zn, and Se of mixtures play an important role in the synthesis and secretion of steroid hormones and mineral absorption metabolism pathway through effects on the expression of the key genes and metabolites in GCs. Meanwhile, these also are required for physiological function and metabolism of GCs. Collectively, our outcomes shed new light on the underlying mechanisms of their effect on follicular growth and GCs molecular physiological function, helping explore valuable biomarkers.